Sistem Pendukung Keputusan Pada Agroindustri Kopi Di Kabupaten Bogor Menggunakan Metode Analytic Hierarchy Process (Ahp) - Neneng Rachmalia Feta; Asep Rahmat Ginanjar; Hasan Basri; Michael Sitorus (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
Coffee commodities are agricultural commodities that have highexport value. Indonesia ranks fourth as the most significant coffee exportingcountry in the world. The main problem that occurs is the availability ofabundant crops, not balanced by proper postharvest processing andmarketing and the absence of farmers partnership with the coffeeprocessing industry. This study focuses on the determination of coffeeagroindustry products using the AHP method and the institutionaldetermination of coffee agroindustry using the exponential comparisonmethod. SPK development will use super decision software. The final resultof this study is the calculation of product determination obtained that instantcoffee has the highest weight of 0.3739, while the institution of coffeeagroindustry shows that establishing cooperation with Hulu - Hilir Industryhas the highest weight, namely 389,637